Post-Pandemic Education: Falling or Preparing for a Jump? - V. V. Bolgova; M. A. Garanin; E. A. Krasnova; L. V. Khristoforova (Высшее образование в России)
Abstract. Relevance. The article provides an overview and analysis of the consequences of changes in the global educational space during the period of action of measures to counter the spread of the new COVID-19 coronavirus infection.The aim of the work was to understand the current state and identify possible trajectories of developmentof educational systems in the “post-pandemic” era. Research methodology and methods. The main methods used in the preparation of the work were methods of analysis and synthesis. The review and understanding of various standpoints on the educational organizations functioning in the situation of emergency introduction of quarantine measures and the uncertainty of their consequences allowed us to summarize the main challenges facing the education system today. The forecasting method was used to systematize the capabilities of universities in overcoming crisis phenomena and determine the strengths that can be used as the basis for the transformation of University management.Results. The analysis of the trajectories of the prospective organization of the educational process at the University of “post-pandemic” time is carried out. The article highlights the main ways of the educational system adaptation to work in the conditions of an unpredictable crisis consequences and presents the authors’ vision of the future of higher education in Russia, which is inextricably linked with the country’s attractiveness in the global educational space.Scientific novelty. The authors systematize the impact of the pandemic on various sectors of the economy, including the education sector. The results of the analysis of the practical experience of educational systems in  the new conditions are presented. Scenarios of educational organizations development in an unfavorable dynamic uncertain environment are shown.Practical significance. The results obtained will be useful in adjusting University management systems and developing strategies for universities to overcome the crisis caused by COVID-19 and its consequences.